Warranty Reserve: Contingent Liability, Information Signal, or Earnings Management Tool? - Cohen, Daniel; Darrough, Masako N.; Huang, Rong; Zach, Tzachi (The Accounting Review, 2011)
ABSTRACT: We examine the information role of accounting disclosures on warranties, utilizing a database that became available due to the requirements of FIN 45. First, because firms use warranty policies as a business strategy to promote their products, a warranty reserve can serve two roles: an information signal regarding product quality, as well as a contingent liability. Consistent with this view, we find that the stock market recognizes that: (1) the warranty reserve contains information about firms’ future performance, and (2) the reserve is a liability. Second, because warranty accruals require estimation of future claims, they can be used as a tool of earnings management. Our evidence indicates that managers use warranty accruals to manage earnings opportunistically to meet earnings targets. Finally, we find that the stock market recognizes the understatement of warranty liabilities of firms that managed earnings.